Relation of Climate Temperature to Intracerebral Hemorrhage Volume - Semai Bek; Tayfun Kaşıkçı; Güray Koç; Erkan Tokgöz; Şeref Demirkaya; Zeki Odabaşı (Türk Nöroloji Dergisi, 2010)
OBJECTIVE: In our study we aimed to investigate the correlation between volumes of intracerebral parenchymal hemorrhage, control of hypertension and daily weather temperature changes. METHODS: Data of total 88 patients (49 male-39 female, age 66.50 ± 15.00) with parenchymal hemorrhage were analysed retrospectively (June 2004-June 2009). Hypertension in medical history, arterial blood pressure levels at the time of referral to our clinic, antihypertensive drug usage, hemorrhage volume measured in computerized tomography and daily highest weather temperature were analysed. RESULTS: There was no correlation between volume of hemorrhage and existence of hypertension and drug usage (p> 0.05). There was no correlation between patients’s age and volume of hemorrhage (p> 0.05). There was no correlation between daily weather temperature and volume of hemorrhage in the normotensive patients according to our results. Furthermore there was statistically significant negative correlation between weather temperature and volume of hemorrhage in hypertensive patients without any effect of being on antihypertensive treatment (correlation factor: -0.254) (p< 0.05). CONCLUSION: The volume of hemorrhage in hypertensive patients with hemorrhagic stroke during colder weather seems to be larger. Thus their prognosis are worse. Probably change in the blood viscosity might be responsible.